Vision of their Revolutionary Leadership (Global Journal of Human-Social Science, 2022)
Their revolutionary leadership is part of the exceptional virtues fruit of the maturity and inclination of the time that he she played him her to live the family atmosphere that you they contribute him her ethical-moral principles in the conformation of its personality
Keywords: the professional's formation - it works martiana - revolutionary leadership - ways of professional performance